2018
DOI: 10.1186/s13073-018-0580-z
|View full text |Cite
|
Sign up to set email alerts
|

T cell dynamics and response of the microbiota after gene therapy to treat X-linked severe combined immunodeficiency

Abstract: BackgroundMutation of the IL2RG gene results in a form of severe combined immune deficiency (SCID-X1), which has been treated successfully with hematopoietic stem cell gene therapy. SCID-X1 gene therapy results in reconstitution of the previously lacking T cell compartment, allowing analysis of the roles of T cell immunity in humans by comparing before and after gene correction.MethodsHere we interrogate T cell reconstitution using four forms of high throughput analysis. (1) Estimation of the numbers of transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…These data made it possible to estimate the average number of cell divisions each transduced clone had undergone before rearrangement of the TCRB locus during thymus differentiation. The value is ∼10; this fits with the estimate for the SCID X1 revertant discussed above (Bousso et al, 2000; Clarke et al, 2018; Fig. 2).…”
Section: Additional and Serendipitous Findingssupporting
confidence: 87%
See 3 more Smart Citations
“…These data made it possible to estimate the average number of cell divisions each transduced clone had undergone before rearrangement of the TCRB locus during thymus differentiation. The value is ∼10; this fits with the estimate for the SCID X1 revertant discussed above (Bousso et al, 2000; Clarke et al, 2018; Fig. 2).…”
Section: Additional and Serendipitous Findingssupporting
confidence: 87%
“…The next question relates to T cell diversity. High-throughput sequencing of T cell receptor beta chain (TCRB) variable diversity joining segments from blood T cells of patients treated in trials 1 or 2 showed that distribution of TCR VB (variable region of TCRB) and JB (joining region of TCRB) element usage and the number of unique TCRB CDR3 sequences were similar to control values in all but one of the seven patients tested (Clarke et al, 2018). These data made it possible to estimate the average number of cell divisions each transduced clone had undergone before rearrangement of the TCRB locus during thymus differentiation.…”
Section: Additional and Serendipitous Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…While successful in substantially improving immune function, two individuals developed acute lymphocytic leukemia resulting from retroviral insertion and activation of the LMO2 proto-oncogene (Hacein-Bey-Abina et al, 2003). Fortunately, the leukemias in turn were successfully treated, but these serious adverse events resulted in work to develop alternative strategies to achieve the beneficial results while preventing or reducing untoward effects (Hacein-Bey-Abina et al, 2014;Clarke et al, 2018). Gene therapeutic approaches for JAK3-deficient and IL7R-deficient SCID are areas for future development.…”
Section: Introductionmentioning
confidence: 99%